Legal Opium Farming in India: Historical and Ethnographic Perspectives - Tavaras, Linas (Vilnius University Open Series, 2025)
This chapter explores legal opium farming in Madhya Pradesh, India, by focusing on legal opium farmers and the complexities of their profession. The chapter is divided into three parts. An historical overview of opium cultivation and consumption in India shows that, throughout centuries, the opium plant has been used in many different ways, including medicinal, recreational, and ritual purposes. The second part focuses on how the Indian government regulates opium cultivation and consumption. In 1985 a still valid bill was passed by the Indian government regulating contemporary opium cultivation, possession, sale, purchasing, transport, and storage. Regulation of this psychotropic substance is outdated and poorly functioning, while the number of illicit drug use or possession cases has only increased in recent years (Mehrotra 2021; Sharma et al. 2017). The third part of the chapter analyses ethnographic data (interviews, photographs and fieldwork observations) gathered in two villages in Madhya Pradesh in August 2021 and February 2022. Farmers not only explained the traditional processes of opium cultivation and the meaning they attribute to opium, but they also shared what problems they were facing in their work, most of which are related to unclear or burdensome Government policies on opium cultivation and the increasing attractiveness of the black market.